Protective Effect of Penetratin Analogue-Tagged SOD1 on Cisplatin-Induced Nephrotoxicity through Inhibiting Oxidative Stress and JNK/p38 MAPK Signaling Pathway. (23rd August 2021) - Wang, Xiao-lu; Wang, Liang; Lin, Fo-lan; Li, Si-si; Lin, Ting-xuan; Jiang, Ren-wang
Abstract : Copper/zinc superoxide dismutase (SOD1) can clear cisplatin- (CP-) induced excessive reactive oxygen species (ROS), but exogenous SOD1 cannot enter cells because of its low biomembrane permeability. Cell-penetrating peptides (CPPs) can rapidly cross plasma membranes. This study is aimed at identifying an efficient and stable CPP-SOD1 and investigating its effects on CP-induced nephrotoxicity. We recombined SOD1 with 14 different CPPs and purified them using an NTA-Ni 2+ column. In in vitro experiments, CPPs-SOD1 cell membrane penetration ability and JNK/p38 MAPK signaling pathway were evaluated using Western blotting. ROS production, mitochondrial membrane potential (MMP), and cell apoptosis were determined using flow cytometry and immunofluorescence staining in VERO and HK-2 cells. For in vivo experiments, mice were administered PSF-SOD1 for 2 h before cotreatment with a single CP injection for an additional 4 days. Blood and kidney samples were collected for renal function assessment (creatinine, urea nitrogen, histopathology, TUNEL assay, and JNK/p38 MAPK signaling pathway). Compared with TAT-SOD1, we found that PSF-SOD1 is more efficient at crossing the cell membrane and is stable after transduction into cells. Pretreatment with PSF-SOD1 inhibited CP-induced apoptosis, ROS generation, and JNK/p38 MAPK activation and restored CP-induced MMP loss in VERO and HK-2 kidney cells. Treatment of mice with PSF-SOD1 inhibited CP-induced serum creatinine, blood urea nitrogen elevation, and JNK/p38 MAPK activation. H&E staining and TUNEL assay indicated that kidney tissue damage was alleviated following PSF-SOD1 pretreatment. Overall, PSF-SOD1 ameliorated CP-induced renal damage by partially reducing oxidative stress and cell apoptosis by regulating JNK/p38 MAPK signaling pathway and might be a better cytoprotective agent than TAT-SOD1.